Effectiveness of Structured Teaching Programme Regarding Prevention of Infection in Hospitalized Neonates Among Nursing Students - Paudyal, Laxmi; Singh, Nitu Kumari; Soti, Harikala; Sah, Indu (Nepal Journal of Health Sciences, 2023)
Introduction: Neonatal infection presents with systemic signs of infection and the detection of bacteria or other pathogens in the bloodstream. Infants are particularly vulnerable to bacterial sepsis, and the incidence of sepsis in the neonatal intensive care unit surpasses that of any other hospital department. Educating caregivers through instructional programs can prove beneficial in preventing these infections.Objective: The aim of the study was to assess the effectiveness of a structured teaching program in preventing infection in hospitalized neonates.Methods: A study was conducted among 96 nursing students enrolled in a bachelor-level nursing program at a selected nursing college in Pokhara. The students were chosen using a complete enumerative sampling technique to ensure a diverse group. Data was collected from the nursing students using a self-administered semi-structured knowledge questionnaire. The collected data was analyzed using descriptive and inferential statistics.Results: The findings indicate that 56.25% of the participants possess a moderately adequate level of knowledge, while 31.25% have an inadequate knowledge level in the pre-test. However, after the post-test, there was a significant increase in the knowledge score, with 75% of the respondents demonstrating an adequate level of knowledge. The structured teaching program proved to be effective in enhancing the knowledge level among nursing students, as evidenced by a t-test value of 16.89 (p